Transmission control protocol based on hop-by-hop for satellite networks - Lu WANG; Yue-mei HU; Li-xiang LIU; Xiao-hui HU (Tongxin xuebao)
A transmission control protocol named TPSN(transmission control protocol for satellite networks)was proposed,which applied asynchronous hop-by-hop ACK,and SNACK based on checking window size to reduce overhead of control message and achieve reliable transmission.In addition,TPSN transmitted load information on the base of hop-by-hop scheme to maintain high network resources utilization,fairness among different data flows with heterogeneous RTT and congestion free.The good performance of TPSN,in terms of link utilization,transmission effectiveness and fairness,was verified via a simulated satellite network with high link error rate,large delay and intermittent links.